Studi Akidah Akhlak Tentang Nilai Baik dan Buruk - Ira Suryani; Hasan Ma’tsum; Sri Baniah; Supriadi Supriadi (Medan Resource Center, 2021)
Akidah is an element - a basic element of human belief as a belief system that describes the essence and source of religion. Meanwhile, morals are part of an ethical system that describes the direction and goals that religion wants to achieve. A good Muslim is one who has a straight and strong aqidah that guides him to carry out the Shari'a which is only aimed solely at Allah so that a commendable piety is reflected in him. Akidah and morals are closely related. Aqidah that is strong and true is reflected in the praiseworthy character he has and vice versa. In the conception of Islam, akidah morality is not only a medium that includes human relations with Allah SWT, but also includes relationships with humans and others or with their natural surroundings because Islam is truly Rahmatan lil 'aalamin. If these relationships can be implemented in harmony then that is what is meant by the true implementation of morals in a life that makes the world and the hereafter happy. Islam will reward those who have good morals and reward them with good rewards. Adorning oneself with good morals and piety will enter a person into heaven, because piety will benefit the servant and his master, while good morals will benefit between servants and fellow humans.